Specialty palliative care use among cancer patients: A population-based study. - J Brian Cassel; Donna McClish; David Buxton; Leanne Yanni; Seth Roberts; Nevena Skoro; Peter May; Egidio Del Fabbro; Danielle Noreika (PLoS ONE)
Background Rigorous population-based assessments of the use of specialty palliative care (SPC) in the US are rare. Settings/subjects This study examined SPC use among cancer patients in a mid-sized metropolitan area in Southeast US. Measurements In this cancer decedent cohort study, data were acquired and linked from the state-wide cancer registry; state-wide hospital discharge dataset; and local SPC providers. Results 12,030 individuals with cancer were included in this study; only 2,958 (24.6%) used SPC. Of the 9,072 persons who did not use SPC, 3,877 (42.7%) went only to hospitals that did not offer SPC; and 3,517 (38.8%) went to hospitals that offered SPC but did not use it. About half of SPC recipients (1493; 50.5%) first received SPC in the final 30 days of life, including 768 (26.0%) in the final week of life. Characteristics associated with using SPC use included being in an socio-economic status quintile other than the lowest; being younger; being Black; having a solid (versus hematological) cancer; having a shorter survival with cancer; dying in the latter two years of the study; being from an area of low or complete rurality; having a hospital admission in the final 60 days prior to initiation of PC or death; having more days in hospital; and living within 15 miles of a hospital offering SPC. Conclusions In this population-based study, only one-quarter of cancer patients used SPC, and for half who did so, it came in the final 30 days of life.